2015
DOI: 10.14432/j.macvetrev.2014.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Selected Indicators of Dairy Cattle Welfare in Macedonia

Abstract: The welfare state of cattle in dairy farms in Macedonia has never been assessed previously. The objective of this study was to perform screening analysis of dairy cows welfare and to test the practical implementation of the Welfare Quality ® Assessment protocol for cattle in dairy farms in Macedonia. In ten small scale and large scale tie stall farms 23 measures were recorded related to 9 welfare criteria of 4 welfare principles (WP) described in the Welfare Quality ® Assessment protocol for dairy cows. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
1
12
2
Order By: Relevance
“…The prevalence of cows with dirty udders (27.3%) on farms in this study were lower than assessments conducted in Algeria on part time tie stall housing systems where 62.6% of cows had dirty udders and assessments in Macedonia on tie stall housing systems that found a prevalence of dirty udders to be 65.2% (Benatallah et al, 2015, Radeski et al, 2015. Part of this difference in udder hygiene differences could be due to the differences in housing types (tie stall vs. free-stall and loose housing).…”
Section: Figure 2 Mean Lying Bout Duration (Min/bout ± Sd) By Farm Acontrasting
confidence: 65%
See 1 more Smart Citation
“…The prevalence of cows with dirty udders (27.3%) on farms in this study were lower than assessments conducted in Algeria on part time tie stall housing systems where 62.6% of cows had dirty udders and assessments in Macedonia on tie stall housing systems that found a prevalence of dirty udders to be 65.2% (Benatallah et al, 2015, Radeski et al, 2015. Part of this difference in udder hygiene differences could be due to the differences in housing types (tie stall vs. free-stall and loose housing).…”
Section: Figure 2 Mean Lying Bout Duration (Min/bout ± Sd) By Farm Acontrasting
confidence: 65%
“…These authors found that cows in tie-stalls With rubber mattresses and partial access to pasture were more likely to be dirty than cows housed in tie stalls with straw bedding and without pasture access. A similar study was conducted in Macedonia on farms with tie-stall systems that found high prevalence of poor udder hygiene, hock injuries and moderate lameness (Radeski et al, 2015).…”
Section: Figure 2 Mean Lying Bout Duration (Min/bout ± Sd) By Farm Amentioning
confidence: 71%
“…Regarding AW research, several studies were conducted which related to animal slaughtering, transport, animal behavior, etc. On a national level, the most important studies were the welfare assessment of poultry and dairy farms for the first time in Macedonia (8, 9). AW concerns about ambient conditions and air quality in the poultry and pig farms in the country were also raised.…”
Section: Introductionmentioning
confidence: 99%
“…), although Radeski et al . () recommended use of the full cattle protocol in the Former Yugoslav Republic of Macedonia. The protocols used in this project were adapted to the shorter time available and provided a useful range of information (data) in all species, but would be unsuitable for deriving the integrated Welfare Quality® criterion‐, principle‐ or overall‐scores.…”
Section: Discussionmentioning
confidence: 99%
“…Animal welfare assessments in existing farm assurance schemes in the UK have usually been limited to 20-30 min due to time and financial constraints . Other groups have investigated the effect of shortening the Welfare Qualityâ protocols (Heath et al 2014;De Jong et al 2016), although Radeski et al (2015) recommended use of the full cattle protocol in the Former Yugoslav Republic of Macedonia. The protocols used in this project were adapted to the shorter time available and provided a useful range of information (data) in all species, but would be unsuitable for deriving the integrated Welfare Qualityâ criterion-, principle-or overall-scores.…”
Section: Challenges Limitations and Opportunitiesmentioning
confidence: 99%